Development of Android-Based Interactive Learning Media with SAC Integrated PBL Model on Temperature and Heat Materials - Miranda, Agustina; Nanda, Nanda Novita; Tulus, Tulus Setiawan; Syafrizal, Syafrizal; Widya, Widya (CV. Media Inti Teknologi, 2025)
This study aims to develop interactive learning media based on android integrated with PBL model to improve students' critical thinking skills. Interactive learning media based on android developed with SAC based on PBL model is one type of interactive multimedia teaching material containing images, texts, and videos that are systematically arranged according to PBL model syntax which is useful for improving students' critical thinking skills. The purpose of this study was to evaluate the feasibility and benefits of using interactive learning media products based on android as a tool to help students of class XI SMA N 2 Lhokseumawe in studying temperature and heat material. The ADDIE paradigm is used in this development research to refer to the research and development (R&D) approach. The subjects of the study were physics teachers and students of SMA N 2 Lhokseumawe. The results of the study are as follows: 1) Media validation obtained a percentage of 82.5% with the category